Analisis Penyebab Tanah Longsor di Kalitlaga Banjarnegara - Apriyono, Arwan (Jenderal Soedirman University, 2009)
Indonesia is one country that has many areas vulnerable to landslides. To the present time, there are many victims of disasters caused by landslides in Indonesia. To handle the landslide disaster, requires some knowledge about the causes, mechanisms and appropriate mitigation efforts against disasters mentioned above. Causes and mechanisms of landslides is necessary in determining the mitigation in order to the victim can be minimized.This paper is an analytical study of the causes of landslides at Kalitlaga Village, Pagentan Sub district, Banjarnegara Regency. Causes of landslides determined by analyzing the results of field investigation and supporting data (topographic and geological maps at the research location). The analysis results, also be used to determine the proper method of handling landslides in the area. Based on the results investigation field, it can be concluded that the main cause of landslides at Kalitlaga is topographic factors. Kalitlaga Village is located in the mountain range with a fairly steep slope ranges from 20o - 45o. The other cause of landslides is a poor drainage system in the village. Besides, based on geological maps, geological structure in the area included breksi rock in tapak formation, which has a sandstone soil type, breksi andesite composition and the organic soil. The characteristics of this soil type have a low cohesion value with a high permeability, so that condition also supports the occurrence of landslides. Kalitlaga landslide in the village can be minimized by manage the drainage system. Besides, efforts such as cutting of the slopes also need to be done at some location.